Med Aromat Plants 2019
DOI: 10.35248/2167-0412.19.8.335
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Fingerprint of Greek Sideritis spp.: Implications for Potential Drug Discovery and Advanced Breeding Strategies

Abstract: Plant species of the Sideritis genus are native to the Mediterranean region and widely used through millennia for their medicinal and culinary properties. They are mostly known as mountain tea or Shepard tea and in the last few years, they are on the spotlight due to the production of an enormous variety of bioactive secondary metabolites exerting a wide range of pharmaceutical applications. In the present study the biochemical value and the health promoting components of various indigenous Sideritis species w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Previous comparisons among Sideritis species also found that S. scardica samples had higher TPC than S. raeseri [ 5 ]. Overall, the values of total phenolics and total flavonoids herein were comparatively equal [ 40 ] or lower in comparison with previous studies [ 4 , 5 , 14 , 34 , 40 ] and the differences could be attributed to the extraction method, as well. The high content of total phenols and flavonoids of SR was depicted in its high antioxidant activity in both FRAP and DPPH assays.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous comparisons among Sideritis species also found that S. scardica samples had higher TPC than S. raeseri [ 5 ]. Overall, the values of total phenolics and total flavonoids herein were comparatively equal [ 40 ] or lower in comparison with previous studies [ 4 , 5 , 14 , 34 , 40 ] and the differences could be attributed to the extraction method, as well. The high content of total phenols and flavonoids of SR was depicted in its high antioxidant activity in both FRAP and DPPH assays.…”
Section: Resultsmentioning
confidence: 85%
“…Kostadinova et al [ 49 ] also supported that sesquiterpenes were in high concentrations, indicating germacrone, elemol acetate, and a-cadinol as the prevalent compounds. Β-Caryophyllene was also found in high concentrations in two Greek populations of cultivated SR [ 5 ]), whereas α-bisabolol and bicyclogermacrene were found in the population originating from Florina. Observations of great variety in essential-oil composition of close Greek SR populations (both from Kozani) have been made by Kloukina et al [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species S. scardica and S. raeseri appear poorer in terms of mineral content, and demonstrate almost half the quantities of the majority of nutrients as K, P, Ca, Mg (Karapandzova et al, 2013), compared to S. cypria. Trikka et al (2019) evaluated different species of Sideritis genus from different geographical regions of Greece and plants exhibited high variability, even within species (S. perfoliata, S. scarica, S. raeseri), and had lower contents in minerals than S. cypria. These variations may be the effect of the cultivation practices applied or/and the harvesting periods (Chrysargyris et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Related species of the genus Sideritis, namely S. scardica [ 22 , 29 , 72 ], S. clandestina (Bory and Chaub.) Hayek [ 21 ], S. raeseri [ 72 , 73 , 74 ], and S. syriaca L. [ 22 ], whose aerial parts have been traditionally used for the treatment of inflammation, gastrointestinal disorders and cough associated with cold and whose usage has been approved by the European Medicines Agency (EMA) Committee on Herbal Medicinal Products (HMPC) [ 75 ], were observed to possess, as one of their major volatile constituents, the same VOCs that were found in S. romana and S. montana in the present study, thus, indicating a promising potential for future investigations of these species.…”
Section: Discussionmentioning
confidence: 99%